The Discussion of the Future of the European Union in the 21st Century (Czech Journal of International Relations, 2002)
The European Union (EU) is facing several challenges connected with the new millennium aswell as with a new paradigm. The EU is searching for its new identity and new visions. Among them is also the answer for solving the dichotomy of the future settlement of Europe either on federal,supranational or intergovernmental levels.These new phenomena and the effort to bring the EU closer to the citizens together with the new tasks brought the EU to begin a discussion about the future of Europe and its final settlement called finalite. The Summit of the European Council, which was held in Nice in December 2000, stated in the Declaration of the Future of the EU that the reforms needed for the enlargement are ready and the path for the accession of the new members is open. The conference called for a broad and deep discussion about the future of the EU. The Swedish and Belgian Presidencies together with the Commission and with the help of the European Parliament were asked to include representatives of the national parliaments and all other opinion makers from political, economic, academic circles, representatives of civil society and others into a broad discussion. The participation of the candidate countries needs to be clarified during the discussion itself. The task to launch the discussion was begun the Swedish Presidency. The first step was a report from the conference of the European Council in Göteborg in June 2001. The results of which would be used by the summit in Belgian Laeken in December 2001.The results will be evaluated and the ways of realization would be identified by the Intergovernmental Conference in 2004. The conference is also supposed to bring changes in EU Treaties. Knowing the importance of showing further ways for the development of Europe started the discussion about its future. Statesmen, politicians and political scientists have given their opinions.What is the EU going to look like in the third millennium?The models of further European development are oscillating between the federal model (Schröder) on one hand, and the intergovernmental model (Blair) on the other. Mostly, however they fall somewhere in between, asking for a federation of national states (Jospin, Chirac, Fischer). This term, though, presents something of an oxymoron full of antagonism.